2009
DOI: 10.1002/jnr.22062
|View full text |Cite
|
Sign up to set email alerts
|

Sex influences the effect of a lifelong increase in serotonin transporter function on cerebral metabolism

Abstract: Polymorphic variation in the human serotonin transporter (SERT; 5-HTT) gene resulting in a lifelong increase in SERT expression is associated with reduced anxiety and a reduced risk of affective disorder. Evidence also suggests that sex influences the effect of this polymorphism on affective functioning. Here we use novel transgenic mice overexpressing human SERT (hSERT OVR) to investigate the possible influence of sex on the alterations in SERT protein expression and cerebral function that occur in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…At 10 min after 8-OH-DPAT, or 20 min after DOI, 5 μCi [ 14 C]-2-deoxyglucose in 0.4 ml 0.9% NaCl was injected intraperitoneally. After 45 min, mice were decapitated and their brains analyzed by quantitative autoradiographic imaging, as described previously [54,55]. …”
Section: Methodsmentioning
confidence: 99%
“…At 10 min after 8-OH-DPAT, or 20 min after DOI, 5 μCi [ 14 C]-2-deoxyglucose in 0.4 ml 0.9% NaCl was injected intraperitoneally. After 45 min, mice were decapitated and their brains analyzed by quantitative autoradiographic imaging, as described previously [54,55]. …”
Section: Methodsmentioning
confidence: 99%
“…Further, thalamocortical 5-HT 1B signaling also modulates responsiveness to axon guidance cues (Bonnin et al, 2007). Beyond structural disruption, indirect measures of somatosensory function in various serotonin transporter mouse models indicate altered processing of whisker stimulation (Esaki et al, 2005, Dawson et al, 2009). In parallel, other groups have found that serotonin also impacts visual and auditory cortex development and function (Salichon et al, 2001, Simpson et al, 2011).…”
Section: Serotonin and Neurodevelopmentmentioning
confidence: 99%
“…5,37 Rats were injected i.p. with 4.625MBq kg À1 of [ 14 C]-2-DG (Sigma-Aldrich) at a steady rate over a 10-second period before being returned to their home cage.…”
Section: Semiquantitative 14 C-2-dg Autoradiographic Imagingmentioning
confidence: 99%
“…Error, punishment, and perseverative responding data were analyzed using 1-way ANOVA with Tukeys post hoc test for multiple comparisons. Regressive error data were analyzed using 2-way repeated measures ANOVA with the within-subject factor as the trial level (1)(2)(3)(4)(5) and the between-subject factor as drug treatment group. Tukeys post hoc test was applied to investigate differences between treatment groups at each trial level.…”
Section: Attentional Set-shifting Taskmentioning
confidence: 99%
See 1 more Smart Citation